WNT16 from decidual stromal cells regulates HTR8/SVneo trophoblastic cell function via AKT/beta-catenin pathway. Issue 5 (10th March 2022) - Li, Xinyi; Shi, Jiaxin; Zhao, Weijie; Huang, Xixi; Cui, Liyuan; Liu, Lu; Jin, Xueling; Li, Djin; Zhang, Xuan; Du, Meirong
Abstract : Decidual stromal cells (DSCs) modulate the function of trophoblasts through various factors. Wnt signaling pathway is active at the maternal–fetal interface. Here, we isolated endometrial stromal cells (ESCs) from women of reproductive ages and DSCs from normal pregnancy during the first trimester (6–10 weeks). Real-time quantitative PCR and western blotting were used to screen out the most variable WNT ligands between ESCs and DSCs, which turned out to be WNT16. Both culture mediums from DSCs and recombinant protein of human WNT16 enhanced the survival and invasion of HTR8/SVneo trophoblastic cells. Furthermore, the regulation of DSCs on trophoblast was partly blockaded after we knocked down WNT16 in DSCs. Treating HTR8/SVneo trophoblastic cells with small molecular inhibitors and small interfering RNA (siRNA), we found that the activity of AKT/beta-catenin (CTNNB1) correlated with the effect of WNT16. The crosstalk of WNT16/AKT/beta-catenin between DSCs and trophoblasts was determined to be downregulated in unexplained recurrent spontaneous abortion. This study suggests that WNT16 from DSCs promotes HTR8/SVneo trophoblastic cells invasion and survival via AKT/beta-catenin pathway at the maternal–fetal interface in human early pregnancy. The disturbance of this crosstalk between DSCs and trophoblasts might cause pregnancy failure.